Combination hemodialysis and centrifugal therapeutic plasma exchange: 18 years of Canadian experience. Issue 2 (28th August 2012) - Farah, Myriam; Levin, Adeera; Kiaii, Mercedeh; Vickars, Linda; Werb, Ron
Abstract: Hemodialysis (HD) and therapeutic plasma exchange (TPE) are extracorporeal treatments that may both be required in the same patient. When provided separately, 7–8 hours of therapy time is required. Simultaneous administration of both therapies can reduce time and personnel requirements. We report our 18‐year institutional experience with combination HD and centrifugal TPE therapy. During combination therapy, the TPE circuit is attached to the HD circuit through an extension blood line connected to the HD venous return line, allowing simultaneous operation of both circuits. The HD circuit is anticoagulated with heparin and the TPE circuit with regional citrate. Blood flow rates through the HD circuit can reach 350 mL/min with plasma removal rates in the TPE circuit up to 60 mL/min. Ninety‐two patients received a total of 621 treatments between December 1993 and July 2011. All treatments were completed within 4 hours. No major treatment‐related adverse events occurred and less than 10% of treatments were complicated by minor events. Main indications for treatment were ANCA (anti‐neutrophilic cytoplasmic antibody) vasculitis (n = 25), Goodpasture's/antiglomerular basement membrane disease (n = 24), adult thrombotic thrombocytopenic purpura/hemolytic uremic syndrome (n = 24), and acute antibody‐mediated renal transplant rejection (n = 8). Overall rates of renal recovery, in‐hospital mortality, and overall mortality at 18‐year follow‐up were 45% (41/ 92), 2% (2/92), and 21% (19/ 92), respectively, compatible with published literature. Combination HD and TPE is safe, efficient, and requires less human resources and time than conventional sequential therapy. It should be considered in patients whose treatment regimen includes HD and TPE.